2023
DOI: 10.1002/berj.3906
|View full text |Cite
|
Sign up to set email alerts
|

‘I make a lot of the choices myself—I think I've taught myself that through the imbalance of support’: The internal conversations, reflexivity and post‐school educational achievement of care‐experienced young people

Elaine Matchett,
Peter Appleton

Abstract: The percentage of care‐experienced young people in England progressing to university by the age of 19 currently stands at around 12–13% with a further 10% of care‐experienced adults attending university during their 20s and 30s. This figure remains lower than both the general population and other groups of disadvantaged learners. It is well established that the educational attainment of care‐experienced young people can be impacted by a range of barriers to learning. Existing research often focuses on the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Such circumstances can understandably impinge on care-experienced peoples' engagement with, perceptions of and outcomes in education. Stability formed through trusting relationships with adults and stable living circumstances, as two of our sociological contributions highlight (Matchett & Appleton, 2024;Mølholt et al, 2024), are highly influential in educational success among care-experienced people. In applying Luhmann's (1988) theory of 'trust, risk and uncertainty' to care-experienced people transitioning out of care in Denmark, Mølholt et al (2024) found that three modes of future expectations existed among their participants: 'trust, risk and danger'.…”
Section: Content Of This Speci Al Issuementioning
confidence: 95%
See 4 more Smart Citations
“…Such circumstances can understandably impinge on care-experienced peoples' engagement with, perceptions of and outcomes in education. Stability formed through trusting relationships with adults and stable living circumstances, as two of our sociological contributions highlight (Matchett & Appleton, 2024;Mølholt et al, 2024), are highly influential in educational success among care-experienced people. In applying Luhmann's (1988) theory of 'trust, risk and uncertainty' to care-experienced people transitioning out of care in Denmark, Mølholt et al (2024) found that three modes of future expectations existed among their participants: 'trust, risk and danger'.…”
Section: Content Of This Speci Al Issuementioning
confidence: 95%
“…While the papers within this special issue cover an interesting variety of topics individually, when taken together, the commonalities between them highlight pertinent issues experienced by those with a background of care across educational settings and national contexts. These include inclusivity and recognition in the definitions used to identify someone as 'care-experienced' (Brown & Shelton, 2024;Bunn & Fuller, 2024;Child & Marvell, 2024), the importance of relationships for educational success (Brown & Shelton, 2024;Collins et al, 2024;Marion & Tchuindibi, 2024;Matchett & Appleton, 2024;Sandford et al, 2024) and the risk-laden nature of transitions through education for those with an absence of support (Melkman, 2024;Mølholt et al, 2024).…”
Section: Content Of This Speci Al Issuementioning
confidence: 99%
See 3 more Smart Citations